Is Perception Reality? Improving Agricultural Messages by Discovering How Consumers Perceive Messages - Joy N. Goodwin; Christy Chiarelli; Tracy Irani (Journal of Applied Communications, 2011)
This study assessed how consumers interpret agricultural messages typically found on commodity organizations’ websites in Florida. Four focus groups were held in the fall of 2010. Results indicate that the participants found most of the messages to be unfavorable, rather than favorable. Additionally, the conclusions made by the participants were explained as being influenced by previous experience, corporate influence, history, the creation of mental images, lack of supporting information, and media influence. Participants provided researchers with suggestions to improve the messages and create a more favorable response from consumers. Further research should be done in this area to continue to improve the effectiveness of agricultural messages. In addition, this research should be replicated in other geographic locations. The implications of this study provide valuable information for agricultural communicators, commodity organizations, industry professionals, and those wanting to tell the story of agriculture.
Keywords: agricultural communication; framing; social cognitive theory; messages; commodity organization